Diagnostic bias during the COVID-19 era: COVID-19 or renal abscess?. Issue 3 (August 2021) - Amato, Marco; Eissa, Ahmed; Rosiello, Giuseppe; Farinha, Rui; Piazza, Pietro; Sighinolfi, Maria Chiara; Rocco, Bernardo; Bianchi, Giampaolo; Micali, Salvatore; Mottrie, Alexandre; Puliatti, Stefano
Introduction: The Coronavirus disease-2019 (COVID-19) has been declared as a pandemic in March 2020 by the World Health Organization (WHO). Since then, this pandemic has dramatically affected the entire world, even radically influencing the way patients are framed at triage. Symptoms and tests in most cases lead to a correct diagnosis; however, error may be around the corner. Case report: A 60 years old patient was referred with weight loss, fatigue and mild fever for 3 weeks as he was working in a COVID-19 ward. After a positive swab and chest CT scan, he was admitted in the hospital and treated as mild COVID-19 patient. A CT scan performed after the patient was discharged revealed a renal lesion misidentified as a tumor then clarified to be an abscess which retrospectively appears to be the main cause of his symptoms. Conclusion: Clinicians should consider other life-threatening disease in the differential diagnosis of patients presenting with similar symptoms to minimize mistakes and avoid further unnecessary investigations.